Overexpression of mitochondrial oxodicarboxylate carrier (ODC1) preserves oxidative phosphorylation in a yeast model of Barth syndrome - Maxence de Taffin de Tilques; Déborah Tribouillard-Tanvier; Emmanuel Tétaud; Eric Testet; Jean-Paul di Rago; Jean-Paul Lasserre (The Company of Biologists, 2017)
Cardiolipin (CL) is a diglycerol phospholipid mostly found in mitochondria where it optimizes numerous processes, including oxidative phosphorylation (OXPHOS). To function properly, CL needs to be unsaturated, which requires the acyltransferase tafazzin. Loss-of-function mutations in this protein are responsible for Barth syndrome (BTHS), presumably because of a diminished OXPHOS capacity. Here, we show that overexpressing Odc1p, a conserved oxodicarboxylic acid carrier located in the mitochondrial inner membrane, fully restores oxidative phosphorylation in a yeast model (taz1Δ) of BTHS. The rescuing activity involves the recovery of normal expression of key components that sustain oxidative phosphorylation, including cytochrome c and electron transport chain complexes IV and III, which are strongly downregulated in taz1Δ yeast. Interestingly, overexpression of Odc1p was also shown previously to rescue yeast models of mitochondrial diseases caused by defects in the assembly of ATP synthase and by mutations in the MPV17 protein that result in hepatocerebral mitochondrial DNA depletion syndrome. These findings define the transport of oxodicarboxylic acids across the inner membrane as a potential therapeutic target for a large spectrum of mitochondrial diseases, including BTHS.